2017
DOI: 10.21608/ejchem.2017.1463.1095
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal characterization of water quality in the Ouémé River basin (Republic of Benin, West Africa)

Abstract: T HE STUDY aims at evaluating the quality of the water in the Ouémé River basin. Data were collected from October 2014 through September 2015. Physico-chemical parameters were assessed and the concentrations of dissolved heavy metals were determined. The results show both physical and chemical pollutions of the water according to a nonlinear pollution gradient. The middle basin up to the height of the city of Kaboua appears to be the most polluted segment. The Delta region, near the coast, is the second most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Manganese, chromium, and nickel had values that exceeded limits only during the dry months. This observed trend could also be attributed to season and anthropogenic influences as observed in iron, lead, and cadmium (Etesin et al, 2013;Houssou et al, 2017;Haque et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Manganese, chromium, and nickel had values that exceeded limits only during the dry months. This observed trend could also be attributed to season and anthropogenic influences as observed in iron, lead, and cadmium (Etesin et al, 2013;Houssou et al, 2017;Haque et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Grützmacher et al (2013) and CGWB (2014) defined geogenic sources as levels that exceeded permissible limits without any direct or indirect link to anthropogenic activities and could have negative health effects. Little or no precipitation, low flow rate, higher air temperatures, and higher evaporation during the dry months contribute to the concentration and higher values of the metals (Etesin et al, 2013;Houssou et al, 2017;Haque et al, 2019). The dry periods or seasons are also associated with increased human visitations and activities because rivers and streams are major sources of water for drinking and most domestic activities in the region (Onyele and Anyanwu, 2018;Anyanwu and Umeham, 2020a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal variations observed could be attributed to low precipitation, higher atmospheric temperatures resulting in higher evapotranspiration rates leading to concentration and higher values in the dry season while lower values during the wet season may be due to dilution by rain water (Atobatele & Olutona, 2013;Etesin et al, 2013;Houssou et al, 2017). Zinc and copper were generally low and within limits.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures were recorded between December 2019 and February 2020, which was the peak of the dry season. In the tropics, the wet season results in lower water temperatures while the dry season brings about higher temperatures (Anyanwu, 2012;Etesin et al, 2013;Houssou et al, 2017). Idowu et al (2013) reported that the higher water temperatures recorded during the dry season could be as a result of low precipitation, high atmospheric temperature and low relative humidity.…”
Section: Discussionmentioning
confidence: 99%